Fabrication of Carbon Nanotube Field Effect Transistor Using Dielectrophoresis and Its Application as Static Random Access Memory Bit Cell - Kareer, Shobhit (Université d'Ottawa / University of Ottawa, 2019)
The aim of the thesis is to fabricate Schottky contact carbon nanotube field effect transistor (CNFET) using the dielectrophoresis (DEP) to resolve the alignment issue and show its transistor behaviour. The work presented is a combination of fabrication and simulation of CNFET. Fabrication of the device electrode had been done using the electron beam lithography to achieve a channel length of 150nm and analysis was done on an optical microscope, SEM, AFM and Raman spectroscopy. Second half of the thesis provides a solution to “bottleneck communication” between microprocessor and memory to increase the computation for applications like AI, IoT etc and 3D monolithic memories. As a solution, we propose a novel CNFET based processing in-memory architecture using a novel CNFET dual port single-ended SRAM bit cell. The combination of the CNFET and processing in-memory can be a new phase for memory and computation.
Keywords: SRAM; Carbon Nanotube; Nanofabrication